2021
DOI: 10.1016/j.jedc.2021.104208
|View full text |Cite
|
Sign up to set email alerts
|

Banks, money, and the zero lower bound on deposit rates

Abstract: We develop a New Keynesian model where all payments between agents require bank deposits through deposits-in-advance constraints, bank deposits are created through disbursement of bank loans, and banks face a convex lending cost. At the zero lower bound on deposit rates (ZLBD), changes in policy rates affect activity through both real interest rates and banks' net interest margins (NIM). At estimated credit supply elasticities, the Phillips curve is very flat at the ZLBD, because inflationary pressures increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 99 publications
1
2
0
Order By: Relevance
“…Such a relationship between the bank spread and credit growth rate is consistent with the empirical studies of Shin (2010, 2011),Fraisse et al (2020), andKumhof and Wang (2021).4 Several empirical studies have found the evidence supporting the existence of this kind of channel (DiMaggio & Kermani, 2017;Mian et al, 2020;Mian & Sufi, 2018).5 This bank lending channel is also developed from the perspective of loans creating money. However, it is based on the idea that output depends on credit demand, and that credit demand will fall in response to increases in loan rates resulting from policy-induced increases in bank funding costs.…”
supporting
confidence: 77%
“…Such a relationship between the bank spread and credit growth rate is consistent with the empirical studies of Shin (2010, 2011),Fraisse et al (2020), andKumhof and Wang (2021).4 Several empirical studies have found the evidence supporting the existence of this kind of channel (DiMaggio & Kermani, 2017;Mian et al, 2020;Mian & Sufi, 2018).5 This bank lending channel is also developed from the perspective of loans creating money. However, it is based on the idea that output depends on credit demand, and that credit demand will fall in response to increases in loan rates resulting from policy-induced increases in bank funding costs.…”
supporting
confidence: 77%
“…This paper contributes to a broad literature examining nonlinearities in macroeconomic relationships in general (e.g., Auerbach & Gorodnichenko, 2012;Barnichon et al, 2022;Berge et al, 2021;Kilian & Vigfusson, 2011;Santoro et al, 2014;Tenreyro & Thwaites, 2016) and specifically in the Phillips curve (e.g., Ascari et al, 2022;Barnes & Olivei, 2003;Debelle & Laxton, 1997;Hooper et al, 2020;Kumar & Orrenius, 2016). Our paper is related to the recent studies examining whether nonlinearities can explain the missing disinflation (e.g., Beaudry & Portier, 2018;Harding et al, 2022;Kumhof & Wang, 2021). 4 We contribute to this literature by adopting a flexible estimation approach and by examining jointly nonlinearities and consumer expectations.…”
Section: Introductionmentioning
confidence: 92%
“…Nonlinearities can arise due to interest-rate bounds(Beaudry & Portier, 2018;Brunnermeier & Koby, 2018;Kumhof & Wang, 2021), a kinked demand curve(Harding et al, 2022;Kimball, 1995), downward nominal wage rigidity(Daly & Hobijn, 2014), and state dependence in structural parameters such as the Calvo rate(Alvarez et al, 2018;Gagnon, 2009;Petrella et al, 2018). Asymmetries in the transmission of monetary policy and their consequences are examined inSchaling (2004) andSantoro et al (2014).5 The literature emphasizing survey measures of inflation expectations includesLeduc et al (2007),Adam and Padula (2011),Chan et al (2018),Coibion et al (2018), andRoberts (2022), among many others, with some papers emphasizing robust deviations from rationality (e.g.,Andrade & Le Bihan, 2013;Binder, 2017;Bordalo et al, 2020;Ehrmann et al, 2017;Fuhrer, 2018;Pfajfar & Santoro, 2013).…”
mentioning
confidence: 99%